PENGARUH PENGETAHUAN DAN PERILAKU KEUANGAN TERHADAP PERKEMBANGAN UMKM DI PROVINSI SUMATERA UTARA - januardin Manullang (JEBIM Prima, 2019)
The success of a development is synonymous with the creation of the rate of economic development and the high absorption of labor. One of the real sectors that can reduce unemployment is micro, small and medium enterprises or often abbreviated as MSMEs. In MSME activities, MSME actors must master good financial management to ensure effective financial management. The research consists of independent variables namely financial knowledge (X1) and financial behavior (X2), the dependent variable is the effectiveness of financial management (Y). The purpose of this study is to find out and analyze the influence of knowledge and financial behavior on the development of MSMEs in. The benefits of the research are as input in improving the development of MSMEs, and as one of the requirements in the selection process for admission to the USU Faculty of Economics's Doctor of Management Science Program. This research was conducted in North Sumatra, the approach used in this study was a survey approach, the type of research was quantitative descriptive research, the nature of the research was explanatory research, the population in this study were MSMEs in North Sumatra, namely 2,857,124 MSMEs. the number of research samples is 400 respondents taken randomly by using the Slovin formula, 30 respondents used for valid tests and real tests taken outside the study sample. Data collection techniques were carried out by interviews (interviews), questionnaires, and decomme. This study uses the Statistical Package for the Social Sciences (SPSS) program with a multiple regression equation as follows: Sub Model: Y = a + b1X1 + b2X2 e. F value calculated = 17,015> F table = 3.02 and significance probability 0,000 <0,05, then H1 is accepted, meaning that financial knowledge and behavior simultaneously have a positive and significant effect on the development of MSMEs. The value of t count> t table or 3,633> 0,097, and the significance of 0,000 <0,05, then Ha is accepted, meaning financial knowledge has a positive and significant effect on the development of MSMEs. The value of t count> t table or 4.142> 0.097, and the significance of 0,000 <0.05, Ha is accepted, meaning financial behavior has a positive effect and significance <0.05, Ha is accepted, meaning financial behavior has a positive and significant effect on the development of MSMEs. Keywords: Knowledge, behavior,financial management.